Proceedings of the First ACM/SIGEVO Summit on Genetic and Evolutionary Computation 2009
DOI: 10.1145/1543834.1543948
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of micro-behavior and bounded rationality in double auction markets using co-evolutionary GP

Abstract: We investigate the dynamics of trader behaviors using a co-evolutionary genetic programming system to simulate a double-auction market. The objective of this study is twofold. First, we seek to evaluate how, if any, the difference in trader rationality/intelligence influences trading behavior. Second, besides rationality, we also analyze how, if any, the co-evolution between two learnable traders impacts their trading behaviors. We have found that traders with different degrees of rationality may exhibit diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…13 See Gomez-Barroso et al (2011). Becker and Seshadri (2003), who described how cooperative co-evolution can be used to generate trading rules with genetic programming; more recently, Nie et al (2008), who demonstrated a co-evolutionary computation method to validate reverse multi-attribute auction settings with one buyer and many sellers and, finally, Chen et al (2009aChen et al ( , 2009b, who published two works on the dynamics of trader behaviors using a co-evolutionary genetic programming system to simulate and analyze a double auction market.…”
Section: Methodsmentioning
confidence: 99%
“…13 See Gomez-Barroso et al (2011). Becker and Seshadri (2003), who described how cooperative co-evolution can be used to generate trading rules with genetic programming; more recently, Nie et al (2008), who demonstrated a co-evolutionary computation method to validate reverse multi-attribute auction settings with one buyer and many sellers and, finally, Chen et al (2009aChen et al ( , 2009b, who published two works on the dynamics of trader behaviors using a co-evolutionary genetic programming system to simulate and analyze a double auction market.…”
Section: Methodsmentioning
confidence: 99%